DIDONG SEBAGAI MEDIA PEMBELAJARAN NILAI-NILAI KEARIFAN LOKAL PADA SEKOLAH DASAR: PEWARISAN BUDAYA - Afriadi, Putra; Khairina, Mifta (Universitas Negeri Medan, 2023)
This study aims to analyze the use of Didong in the context of cultural inheritance as an elementary school learning medium. The research method is qualitative with an interdisciplinary approach. The location of the research was at public elementary school 8 Takengon, Central Aceh District. Data sources are primary data sources including artists, librarians and community leaders, then secondary data sources include books and references from previous researchers. Data collection techniques consist of observation, interviews, and document studies. The data validation technique uses data triangulation. Data analysis techniques consist of reduction, data presentation, and data verification stages. The results of the study show that the use of didong in learning local wisdom values in elementary schools has a number of benefits. First, didong provides direct experience to students in understanding their local culture. Second, didong as a learning medium provides opportunities for students to learn local wisdom values, such as respect for parents, mutual cooperation, honesty, and justice. Students through observation and participation in didong performances can recognize these values and understand their significance in everyday life.